Federal Indian Reserved Water Rights and the No Harm Rule - Termyn, Christian (Columbia Journal of Environmental Law, 2019)
Most American Indian rights to water trace their origins to 19th century treaty negotiations with the United States. The 1908 Supreme Court case Winters v. United States established that the federal statutes and treaties setting aside land for Indian reservations also impliedly reserved sufficient water to fulfill the purpose of those reservations. In the century since Winters, the development of a legal doctrine around reserved water rights has centered largely on defining and quantifying the amount of water to which tribes are entitled. With an increasing number of tribes holding quantified water rights, a more recent project (and the broad focus of this Note) seeks to integrate tribal water use within the dominant system of western water law: state prior appropriation doctrine. Where water is scarce, even a slight change in practice by one water user may affect the availability of water to other users of a common source. One challenge facing tribes holding reserved rights is that they are typically entitled to much more water on paper than they currently use. This might sound like a good problem to have, however, it is fundamentally at odds with state prior appropriation doctrine, under which water rights are created and maintained exclusively through actual water use. This and other key differences between the two water law regimes raise intractable questions of on-the-ground administration in water systems stressed by environment conditions and human development. The open issues are as basic as who will make the decisions, and what body of law will apply when reserved rights and state water rights are in conflict. Harold Ranquist, a lawyer in the United States Department of the Interior (“DOI”), issue-spotted some of these key questions in a short paper published in 1972. This Note uses Ranquist’s framing of the issues as a jumping-off point to discuss legal developments in tribal water rights administration in the last fifty years. There are surprisingly few, but two are worthy of attention. First, though administration of tribal rights poses a federal question, for a variety of practical and political reasons the modern trend in the negotiated settlement of reserved rights has been to expressly subject tribal water uses to state administration. The second development is a federal case, United States v. Orr Water Ditch, which adopted a useful framework for approaching injury to state water users resulting from a tribe’s change in use of its water. Part II starts with a brief history of the prior appropriation doctrine, then reviews the reserved rights doctrine and the tension in integrating distinct property rights to a common resource. Reserved rights reflect a concept of water acquisition and ownership wholly at odds with prior appropriation doctrine, yet both rights claim a common resource. Part II also discusses how water rights disputes involving tribal rights are resolved, historically through general stream adjudications, and increasingly through negotiated settlement. Part III addresses potential limitations on the nature of tribal water use. Once the basis and measure of the right is established, what flexibility do tribes have to apply the right to various end uses? This Part summarizes scholarship and case law in general agreement (with some notable exceptions) that a tribal reserved right, once quantified, is not restricted to an antiquated agrarian vision of reservations, but can be flexibly applied to contemporary livelihoods and economic development opportunities. Establishing that reserved rightsholders can change the nature of their water use is prerequisite to exploring limitations based on changes to the character of use, including the timing and location of diversion from the source, as well as consumptive use, return flow, and other variables. Part IV gets to the heart of the question: if a tribe changes the end use of its water right, and consequently affects the rights of other federal or private users in the same system, how will those impacts be adjudicated, according to what law, and by whom? Changing the nature of water use, for instance, from irrigated agriculture to municipal use, may change the amount of water consumed as well as the place, timing and other characteristics of the water right. Any clear answer under controlling federal law is elusive, but might theoretically rest in judge-made law or a legislative solution. The path of least resistance for state water administrators would be simply to apply state substantive and procedural water law to reserved rights. Part IV addresses how many negotiated settlement agreements quantifying tribes’ reserved water rights provide that tribal water use will be administered pursuant to state law. This is not mandated by federal common law, but in ratifying these settlement agreements Congress is creating piecemeal federal authority for application of state law to reserved rights. Also, establishing which body of law applies nonetheless leaves many open questions regarding administration of the unique attributes of reserved rights. Building off the federal district court’s reasoning in Orr Ditch, this Note concludes that where tribal change in water use is subject to state law, courts should be reluctant to find injury to a state water user until the tribe has exercised the full extent of its water right.